2014
DOI: 10.5194/bg-11-4225-2014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of floating chamber and eddy covariance measurements of lake greenhouse gas fluxes

Abstract: Abstract. Fluxes of carbon dioxide (CO 2 ) and methane (CH 4 ) from lakes may have a large impact on the magnitude of the terrestrial carbon sink. Traditionally lake fluxes have been measured using the floating chamber (FC) technique; however, several recent studies use the eddy covariance (EC) method. We present simultaneous flux measurements using both methods at lake Tämnaren in Sweden during field campaigns in 2011 and 2012. Only very few similar studies exist. For CO 2 flux, the two methods agree relative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 42 publications
5
74
0
1
Order By: Relevance
“…During the stratified period, CO 2 fluxes were almost always higher when measured with FC than simultaneous EC measurements, as also found in Eugster et al (2003) and Podgrajsek et al (2014a) (statistical significance tested with Mann-Whitney U test, p < 0.05), although daily median values were, on average, higher when measured with EC than FC ( Table 2). Lower daily median FC fluxes might thus result from discontinuous FC measurements missing important episodic flux events, as suggested by Podgrajsek et al (2014a).…”
Section: Co 2 Flux Comparisonsupporting
confidence: 68%
See 3 more Smart Citations
“…During the stratified period, CO 2 fluxes were almost always higher when measured with FC than simultaneous EC measurements, as also found in Eugster et al (2003) and Podgrajsek et al (2014a) (statistical significance tested with Mann-Whitney U test, p < 0.05), although daily median values were, on average, higher when measured with EC than FC ( Table 2). Lower daily median FC fluxes might thus result from discontinuous FC measurements missing important episodic flux events, as suggested by Podgrajsek et al (2014a).…”
Section: Co 2 Flux Comparisonsupporting
confidence: 68%
“…Higher fluxes during the mixing period could have been more suitable for a comparison between the two methods. Podgrajsek et al (2014a) did not find systematically higher fluxes with EC or FC and found quite good agreement between these two methods for CH 4 fluxes. The EC method has a larger source area (flux footprint) than FC method, which might also affect the flux.…”
Section: Ch 4 Flux Comparisonmentioning
confidence: 68%
See 2 more Smart Citations
“…Chambers can be deployed for shorter time spans (15-60 min) in order to determine the gas flux, or they can be left to equilibrate with the CO 2 partial pressure of surface water (Natchimuthu et al, 2017). The equipment is relatively cheap and easy to use compared to other methods such as eddy-covariance (Podgrajsek et al, 2014;Jammet et al, 2017) or whole-lake addition of gas tracers (Cole and Caraco, 1998;Crusius and 25 Wanninkhof, 2003). The disadvantage, however, is the high work load required to repeatedly lift the chambers manually to evacuate the chamber headspace before each measurement of gas flux with the floating chamber resulting in few and discontinuous measurement series (Podgrajsek et al, 2014).…”
Section: Introductionmentioning
confidence: 99%